Fuel flow control through a fuzzy servomechanism: a comparative analysis - Castano, Victor; Rangel-Miranda, Domingo; Alaniz-Lumbreras, Daniel; Olvera-GonzÃ¡lezb, Ernesto (International Journal of Engineering and Technology, 2014)
The evaluation of a fuzzy expert positioning servomechanism that was applied for controlling fuel flow in an experimental process is presented. Since the conventional control techniques are not sufficient to implement nonlinear control systems, a successful control technique based on human experience was used. A comparative study was made by both Fuzzy Logic Control (FLC) and Proportional Integral Derivative (PID) control algorithms. Fuzzy Logic and PID controllers were designed in Lab view program. The real-time position control which consists of a DC motor into a servomechanism was implemented by using a digital acquisition device (DAQ). The experimental results show that step response and semicircular trajectory on the position servomechanism for controlling fuel using FLC, had a better performance than those derived from PID control scheme.